LIMS data - Inferred stratospheric distribution of NOx and HOx trace constituents and the calculated odd nitrogen budget - Callis, L. B.; Russell, J. M.; Boughner, R. E.; Natarajan, M. (1985)
LIMS, SAMS, SBUV and in-situ data have been used to infer species not measured but which are of photochemical interest, e.g., O(3P), O(1D), NO, N2O5, OH, HO2, ClO and HCl. (LIMS = limb infrared monitor of the stratosphere; SAMS = stratospheric and mesospheric sounder; and SBUV = solar backscattered ultraviolet instrument.) Production and loss of odd nitrogen have been calculated and estimates have been made of the odd nitrogen transport due to adiabatically driven circulation derived from LIMS data. Data used from LIMS include O3, NO2, HNO3, H2O and T. CH4 and N2O were taken from SAMS and the UV solar flux from the SBUV instrument. Species were inferred for periods in October, December, March and May. Results for December are discussed. Results indicate: (1) maximum stratospheric odd nitrogen levels of 25 ppbv; (2) evidence of odd nitrogen transport from the mesosphere appearing at 25 km in the wintertime polar latitudes; (3) the polar night build-up of high levels of N2O5 beginning after the autumnal equinox; and (4) the possibility of large downward fluxes of odd nitrogen into the troposphere during the winter at latitudes poleward of 60 degrees.